The Use of Analytical Network Process (ANP) for the Development Strategy of PT PAL to Support Indonesia's Defence Industry - Khadafy, Mouamar; N Suarsana, I G; Susilawati, Susilawati (Journal of Maritime Studies and National Integration, 2022)
Indonesia's strategic geopolitical position, bridging two continents and two oceans, includes vital straits used by numerous foreign ships along the Indonesian Archipelago Sea Route (ALKI). Its strategic importance poses significant defense and maritime security challenges. To address these, President Joko Widodo has enhanced the Navy's role by leveraging the Indonesian defense industry to position Indonesia as a global maritime axis. PT PAL, a key player in this industry, must develop strategic shipbuilding policies to support this vision. This study aims to analyze and identify optimal strategic policies for PT PAL using the Analytical Network Process (ANP) method and Super Decisions software. The findings indicate that prioritizing the development of the warship division is crucial, as it received the highest weight in defense equipment needs. Consequently, PT PAL should focus on enhancing its warship division to align with Indonesia's maritime defense and security objectives.